EFEKTIVITAS PROGRAM KELUARGA HARAPAN(PKH) DALAM MENGATASI KEMISKINAN DI KELURAHAN KADOLOMOKO KECAMATAN KOKALUKUNA KOTA BAUBAU - Alnamira Alnamira; Askal Basir; Junaid Gazalin (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2022)
The type of research used in this study is a qualitative research with a descriptive approach. Three methods of data collection include observation, interviews, and literature study. Data reduction, data presentation, and drawing conclusions are examples of data analysis procedures in this study. The results show that four indications, including targeting, outreach, objectives, and implementation monitoring, can be used to determine whether it is effective or ineffective. The implementation of the Family Hope Program (PKH) in Kadomoko Village, Kokalukuna District as an effort to alleviate poverty, according to research findings that it has not been targeted by using data from the center, it is necessary to update the data again and submit it to the center. (2) The companion party has carried out the socialization of the program implementation well. (3) Objectives The implementation of the program in several components has been going well, such as awareness of the importance of education, but this is inversely proportional to the awareness of the importance of health. (4) Monitoring of Program Implementation will continue to be carried out. Although there are some field constraints in its implementation, solutions are still being sought such as continuing to provide socialization about PKH.